Capturing menstrual health and hygiene in national surveys: insights from performance monitoring and accountability 2020 resident enumerators in Niamey, Niger - Elizabeth Larson (IWA Publishing, 2021)
Menstrual health and hygiene (MHH) is an emerging public health priority. To support policy and practice, large-scale surveys monitoring water, sanitation, and hygiene and reproductive health have started to incorporate MHH. Insights gained from these surveys are contingent on the quality of the measures used. Performance Monitoring and Accountability 2020 (PMA2020) was one of the first survey programs to include MHH. We undertook four focus group discussions with resident enumerators and one with their female supervisors following the 2018 PMA2020 survey in Niamey, Niger and synthesized their insights on the performance of the MHH measures used. Enumerators reported that questions about menstruation were well tolerated and most were understood conceptually. Discussions identified missing response options for the places used for MHH and suggest that enumerator training should include common brands of menstrual materials to ensure data quality. Further, current questions seeking to capture the privacy and safety of locations used for MHH require modification or more intensive training efforts to consistently capture these concepts. Enumerator perspectives on menstrual needs in Niger highlight topics missing from MHH monitoring. Attending to enumerator expertise has the capacity to strengthen future surveys directed toward understudied health and development challenges such as MHH. HIGHLIGHTS Resident enumerators are a source of expertise on the performance of survey questions.; PMA2020 questions regarding menstrual health and hygiene (MHH) were acceptable to respondents.; Asking respondents to report the ‘privacy’ and ‘safety’ of their menstrual management location was the most challenging question to administer.; Resident enumerators described many MHH needs not captured by PMA2020 questions.;